Recursos didácticos y su aporte en el aprendizaje de corte y confección a estudiantes del Instituto tecnológico Superior “Babahoyo”, cantón Babahoyo, provincia los Ríos - Romero Morales, Grendy Solanda (2017)
In the present investigation titled didactic resources and its contribution in the learning of cutting and confection to students of the Higher Technological Institute "Babahoyo", Canton Babahoyo, Province Los Ríos, in this institution there is a little interest to work activities using didactic resources since Teachers give little importance to apply it because they say it is a waste of time, and that these resources generate that the student does not just memorize, but constantly stimulates their knowledge through the interaction and dynamism that the teacher presents them , becoming this means in a strategy or teaching tool that promotes or motivates the learning of tailoring in the student according to their research needs. It is recognized, in this way, that if in this educational institution the necessary and adequate use of the didactic resources were given, it would impel the educational interaction and nurture the preparation of the teachers. In addition, significant learning in the career of cutting and sewing will be achieved, which is why teachers who also contribute to the creation of new methodologies and designs in the classroom that make classroom teaching and learning more motivating, with the acquisition of knowledge and skills that are useful and applicable to the student in their personal, academic and professional life of the career of tailoring.